UNVEILING MORAL GROWTH IN CHILDREN: AN ANALYSIS OF ENID BLYTON’S FIVE ON HIKE TOGETHER - Djiwandono, Jonathan Imanuel; Sunardi, FX Dono (Hiski Malang, 2025)
Children's literature entertains and imparts moral lessons, shaping young minds by fostering empathy and helping them navigate moral dilemmas. This study aims to explore the moral development of the child characters in Enid Blyton’s novel Five on a Hike Together by applying Jean Piaget’s theory of cognitive development and Lawrence Kohlberg’s theory of moral development. The objectives of the study are: (1) to analyze how the children’s thoughts and actions reflect stages of moral growth, (2) to assess the influence of friendship and cooperation as catalysts for their development. This research is conducted using qualitative methods through close reading and textual analysis, focusing on dialogue, narrative progression, and character interaction. The findings reveal that the characters experience a range of moral dilemmas that encourage them to progress from obedience-based reasoning to more autonomous and principle-based judgments. The analysis shows that both Piaget’s and Kohlberg’s frameworks are effective in tracing the characters’ evolving sense of right and wrong, particularly as they respond to danger, trust, and responsibility. Ultimately, the study highlights how Five on a Hike Together offers a nuanced portrayal of moral growth in childhood through adventure and friendship.